THE LEGAL STATUS AND EVIDENTIARY VALUE OF EXPERT OPINIONS IN CIVIL LITIGATION - Ibragimova , Raykhon (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This thesis examines the legal status and evidentiary value of expert opinions in civil litigation, focusing on their role within modern systems of civil procedure. In contemporary adjudication, the increasing complexity of disputes necessitates the involvement of individuals possessing specialized knowledge beyond the competence of judges. As a result, expert opinions have become a crucial means of proof, directly influencing the establishment of factual circumstances and the delivery of fair and reasoned judgments. The study analyzes the doctrinal foundations of expert participation, including the procedural rights and obligations of experts, their independence, and the legal framework governing their appointment and evaluation. The thesis further explores the discretionary power of judges in assessing expert opinions, emphasizing the principle that no piece of evidence shall have predetermined force. In addition, the research addresses key challenges associated with expert evidence, such as risks to impartiality, methodological deficiencies, and the potential overreliance of courts on expert conclusions.